Dilemmas in animal welfare [ - Appleby, Michael C.; Sandoe, Peter; Weary, Daniel M. (CABI, 2014)
There are endless on-going debates in animal welfare. This book seeks to distil some of the major themes of current debate into one volume edited by internationally known names in the field of animal welfare. Each chapter, written by a leading expert wil discuss in an open-handed way a provocative topic, which will be of interest to anyone concerned with animal welfare. Issues covered include tail docking, pet obesity, isolation vs. group aggression, neutering feral cats and the need to conserve wildlife habitats in the face of wild animal overpopulation.